2021
DOI: 10.4018/ijsds.2021010104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Online Repurchase Intention in a Developing Country

Abstract: This research investigates the factors that influence online repurchase intention in a developing country, focusing on Ghana. The study also investigates the unexplored effect of perceived value on user satisfaction and online repurchase intention. The survey method of data collection was employed. The author used the purposive technique of data collection to collect data from 504 online shoppers in two regions of Ghana. The data were analyzed using the partial least square – structural equation modeling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that CPV positively impacts an individual's intention to repurchase networking services (Kuo et al, 2009 ), participate in repeat online group buying (Hsu et al, 2015 ), or revisit online stores (Fang et al, 2016 ). Furthermore, customer perceived value is a significant factor influencing online shopping repurchase intention (Yang and Lee, 2010 ; Pobee, 2021 ), and it plays a crucial role in enhancing online shopping continuance during the COVID-19 pandemic (Prasetyo et al, 2021 ). As a result, customers are more likely to engage in repeat online purchases once they perceive greater value from their previous online shopping experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have demonstrated that CPV positively impacts an individual's intention to repurchase networking services (Kuo et al, 2009 ), participate in repeat online group buying (Hsu et al, 2015 ), or revisit online stores (Fang et al, 2016 ). Furthermore, customer perceived value is a significant factor influencing online shopping repurchase intention (Yang and Lee, 2010 ; Pobee, 2021 ), and it plays a crucial role in enhancing online shopping continuance during the COVID-19 pandemic (Prasetyo et al, 2021 ). As a result, customers are more likely to engage in repeat online purchases once they perceive greater value from their previous online shopping experiences.…”
Section: Literature Reviewmentioning
confidence: 99%